Psychological well-being among dental undergraduate students in Malaysia - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi (2018)
Background: Dental students are subjected to different levels of stressors during various stages of their study and these stressors may affect their psychological well-being leading to serious psychological distress that may hinder their academic performance. Therefore, this study aimed to determine the prevalence of psychological distress among dental undergraduate students. Methods: A sample of 257 dental students from International Islamic University Malaysia participated in this study. The psychological distress was assessed using the 12-item General Health Questionnaire (GHQ-12). A binary scoring method was used to evaluate responses (i.e. 0-0-1-1). The rate was compared between clinical and preclinical phases of the academic program. Results: The overall prevalence of psychological distress among dental students was found to be 40.1%. Although the rate was higher among female students and in the clinical phase but it was only statistically significant among the female students. Conclusions: Psychological distress is high among dental students which may predispose them to emotional disturbances and academic decline.